Interface Design of SnO2@PANI Nanotube With Enhanced Sensing Performance for Ammonia Detection at Room Temperature - Jia, Anqiang; Liu, Bitao; Liu, Haiyan; Li, Qiufeng; Yun, Yingxia (Frontiers in Chemistry, 2020)
Gas sensor with excellent stability and high response at room temperature, has been drawn many attentions owing to the huge demand. Surface design provides an inspiration to make the sensor device more useful. Here, rich and stable oxygen vacancies contained core-shell structured SnO 2 polyaniline (PANI) nanotube were fabricated via facile electrosping process and Ar plasma treatment. It shows that the induced surface oxygen vacancies would accelerate the PANI shell to generate more protons, which can react with the target Ammonia (NH 3 ) gas and enhance its sensor responsibility. It also finds that the obtained oxygen vacancies can be well protected by the coated PANI shell, subsequently resulting an enhanced and stable gas response. It shows that the room temperature gas response of NH 3 can reach to 35.3 at 100 ppm. Finally, the response-recovery performances of 3 months multiple cycles and multiple cycles demonstrate its good stability. This work indicated that this well designed PANI-T-SnO 2 was a potential way for design ammonia gas sensors.